Suicidal Ideation among Medical Students: A Gender Comparison of Suicidal Ideation among Medical Students (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Suicide is a widespread issue which is demonstrating an upward pattern as of late. Suicide is thought to be the second most basic reason for death in adolescents. The reason for the present research was to contemplate the Level of Suicidal Ideation Between Male and Female Medical students. The Descriptive Study Design was utilized, in which 30 Male and 30 Female Medical students were incorporated. The information on Suicidal ideation was gotten by utilizing Suicidal Ideation Scale created by Devendra Singh Sisodia and Vibhuti Bhatnagar (2011). The example picked were in the age assemble between 18-23 years. The got information was dissected with the assistance of independent't' test. The results showed that Significant difference was found amongst Male and Female Medical students in Suicidal ideation. furthermore, It was discovered that female students are most Suicidal ideation than male Medical students.